أثر مخططات التنمية البلدية في تمويل التنمية المحلية دراسة حالة ولاية المسيلة - - فاطيمة ميلودي (University of M'Sila, 2024)
هدفت هذه الد ا رسة إلى تحليل، قياس وتقييم أثر مخططات التنمية البلدية في تمويل التنمية المحلية بولاية المسيلة للفترة الممتدة من 2008 - 2021 ، تم تحقيق ذلد من خلال توضيح المفاهيم المتعلقة بكلا المتغيرين والعلاقة بينهما نظريا، بالتركيز على مستويات الإدارة المحلية والجانب الإنمايي لها كواههة لتبني أسلوب اللامركزية وتحقيق التنمية المحلية، من ثم قياس أثر مخططات التنمية البلدية في تمويل التنمسة المحلية بولاية المسيلة للفترة الممتدة من 2008 - 2021 ، هنا استخدمنا نوعين من النماذج نماذج Panel Data بمقدر MM_Q اولنموذج الثاني والمتعلق بنماذج بيانات السلاسل الزمنية بمقدر bootstrapping method معالجين بذلك قيمة الأثر على كل من الولاية ككل وأحد بلدياتها. وقد أظهرت نتايج الد ا رسة حجم التمويل الحكومي للجماعات المحلية الداعم للتنمية المحلية، غير أن هذا التمويل لم يجسد لغرضه المنشود من خلال توضيح إشكالية التنمية على أنها إشكالية تسيير لا تمويل، أيضا إتكال للجماعات المحلية على المصادر الخارهية في تمويل التنمية، استخلصت هذه النتايج من خلال عرض إي ا ردات مي ا زنية البلدية المركزية للولاية وكذا تحليل واقع التنمية المحلية من خلال مختلف المشاريع التنموية بالولاية، هذا بالإضافة إلى حجم التأثير السلبي لمخططات التنمية البلدية في تمويل التنمية المحلية.
This study aimed to analyze, measure, and evaluate the impact of municipal development plans on local development financing in M'Sila wilaya for the period 2008-2021. This was achieved by clarifying the concepts related to both variables and the relationship between them theoretically, focusing on the levels of local administration and its development aspect as an interface for adopting decentralization and achieving local development. Then, measuring the impact of municipal development plans on local development financing in M'Sila wilaya for the period 2008-2021. Here, we used two types of models: Panel Data models with MM_QR estimator and the second model related to time series data models with bootstrapping method, thus treating the impact value on both the wilaya as a whole and one of its municipalities. The results of the study showed the extent of government financing for local authorities in support of local development. However, this financing did not materialize for its intended purpose, as it highlighted the problem of development as a management problem, not financing. It also showed the reliance of local authorities on external sources for development financing. These results were extracted by presenting the revenues of the central municipal budget of the wilaya as well as analyzing the reality of local development through the various development projects in the wilaya, in addition to the extent of the negative impact of municipal development plans on local development financing.
Keywords: التنمية المحلية، مخطط التنمية البلدية، طريقة العزوم للإنحدار الربيعي، طريقة التمهيد الذاتي; Local development; municipal development plans; MM-QR; bootstrapping method